2010
DOI: 10.2337/dc10-0147
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Family History of Diabetes Is Associated With a Reduced Risk of Cardiovascular Disease in Women With Type 2 Diabetes

Abstract: OBJECTIVETo investigate whether parental family history of diabetes influences cardiovascular outcomes in type 2 diabetes.RESEARCH DESIGN AND METHODSWe studied 1,294 type 2 diabetic patients (mean age 64.1 years, 51.2% female) recruited to a community-based cohort study from 1993 to 1996 and followed until mid-2006. A data linkage system assessed all-cause and cardiac mortality, incident myocardial infarction, and stroke. Cox proportional hazards modeling was used to determine the influence of maternal or pate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 25 publications
2
24
1
Order By: Relevance
“…Svensson et al [4] showed, in a crosssectional study of a Danish population, that more women than men had a parental transmission of diabetes, with a prevalence ratio of 1.19 (1.10, 1.30); however, this ratio was much lower than our observation of a two-to fourfold higher transmission to daughters than to sons. In the Fremantle Diabetes Study of people with diabetes, there was a marginally higher frequency of women having a family history of diabetes (33%) in comparison to men (29%) [3]. In Europe in general, diabetes is more frequent in men than in women.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Svensson et al [4] showed, in a crosssectional study of a Danish population, that more women than men had a parental transmission of diabetes, with a prevalence ratio of 1.19 (1.10, 1.30); however, this ratio was much lower than our observation of a two-to fourfold higher transmission to daughters than to sons. In the Fremantle Diabetes Study of people with diabetes, there was a marginally higher frequency of women having a family history of diabetes (33%) in comparison to men (29%) [3]. In Europe in general, diabetes is more frequent in men than in women.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes Study of people with diabetes, there was a marginally higher frequency of women having a family history of diabetes (33%) in comparison to men (29%) [3]. In Europe in general, diabetes is more frequent in men than in women.…”
Section: Research Article Diabeticmedicinementioning
confidence: 94%
See 2 more Smart Citations
“…In terms of geographical distribution, a total of 14 articles were from Europe (including two from Germany [9,10], four from Italy [11][12][13][14], one from the Netherlands [15], four from Sweden [16][17][18][19] and three from the UK [20][21][22]), 20 were from the Asia-Pacific region (including three from Australia [23][24][25], 10 from China [26][27][28][29][30][31][32][33][34][35], five from Japan [36][37][38][39][40] and two from Taiwan [41,42]), 13 were from North America (including one from Canada [43] and 12 from the USA [44][45][46][47][48][49][50][51][52][53][54][55]), two were from the Middle East (both conducted in Iran …”
Section: Methodsmentioning
confidence: 99%